Risk factors, characteristics, and outcomes of candidemia in an adult intensive care unit in Turkey - ÖZBEN SADIÇ, BESTE; TİGEN, ELİF; BİLGİN, HÜSEYİN; ÇERİKÇİOĞLU, NİLGÜN; KORTEN, VOLKAN (MOSBY-ELSEVIER, 2017)
Thirty-six patients with candidemia and 37 control patients were included consecutively to determine the characteristics of candidemia episodes. The patients with candidemia had higher mortality with higher Sequential Organ Failure Assessment scores and frequency of use of a central venous catheter, total parenteral nutrition, and broad-spectrum antibiotics; chronic renal failure with replacement therapy; and longer stay in an intensive care unit. Candida albicans was the predominant species followed by Candida glabrata, Candida tropicalis, and Candida parapsilosis. All isolates of C glabrata were itraconazole-resistant. (C) 2017 Association for Professionals in Infection Control and Epidemiology, Inc. Published by Elsevier Inc. All rights reserved.
Keywords: Mortality; Epidemiology; Candida infection; Predisposing factors; EPIDEMIOLOGY; INFECTIONS; MORTALITY